Brucine inhibits proliferation of glioblastoma cells by targeting the G-quadruplexes in the c-Myb promoter - Liu, Qiaochu (J Cancer, 2021)
The proto-oncogene c-Myb plays an important role in cell proliferation, and its upregulation affects the development of glioblastomas. G-quadruplexes are secondary DNA or RNA structures that usually form in the promoter region of oncogenes, including c-Myb, and regulate the expression of these genes. The traditional Chinese medicine, brucine, is a ligand of the G-quadruplexes located in the promoter region of c-Myb. The present study investigated the therapeutic effects and mechanism of action of brucine in U87, LN18, and LN229 cells in vitro and in vivo. Our results showed that brucine suppressed the growth of these cells in vitro by arresting the cell cycle and reducing c-Myb expression. Dual-luciferase reporter assays showed that brucine inhibited c-Myb expression by targeting the guanine-rich sequence that forms G-quadruplexes in the c-Myb promoter. Moreover, U87 tumors were suppressed by brucine in a tumor xenograft nude mouse model. Therefore, brucine is potentially effective for treating glioblastomas.